Current and Potential Developments of Cortisol Aptasensing towards Point-of-Care Diagnostics (POTC) - Zainol Abidin, Azrul Syafiq; A. Rahim, Ruslinda; Md Arshad, Mohd Khairuddin; Mohd Faudzi, Fatin Nabilah; Chun, Hong Voon; Tang, Thean Hock; Marimuthu, Citartan (MDPI, 2017)
Anxiety is a psychological problem that often emerges during the normal course of human life. The detection of anxiety often involves a physical exam and a self-reporting questionnaire. However, these approaches have limitations, as the data might lack reliability and consistency upon application to the same population over time. Furthermore, there might be varying understanding and interpretations of the particular question by the participant, which necessitating the approach of using biomarker-based measurement for stress diagnosis. The most prominent biomarker related to stress, hormone cortisol, plays a key role in the fight-or-flight situation, alters the immune response, and suppresses the digestive and the reproductive systems. We have taken the endeavour to review the available aptamer-based biosensor (aptasensor) for cortisol detection. The potential point-of-care diagnostic strategies that could be harnessed for the aptasensing of cortisol were also envisaged.